PENERAPAN PENDEKATAN SAINTIFIK DENGAN MEDIA VISUAL DALAM PENINGKATAN HASIL BELAJAR IPS TENTANG PERJUANGAN PARA TOKOH MEMPERSIAPKAN KEMERDEKAAN PADA SISWA KELAS V SD NEGERI WATUDUWUR TAHUN AJARAN 2015/2016 - Hertantiani, Hikmah (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Scientific Approach Using Visual Model in Improving Social Science Learning about the Strugle in Preparing Indonesian Independence for the Fifth Grade Students of SDN Watuduwur in the Academic Year of 2015/2016. The objectives of this research is  to improve social science learning about the Strugle in Preparing Indonesian Independence This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 35 students of the fifth  grade of SD Negeri Watuduwur. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Source of data were derived from students, teacher, and observer. Techniques of collecting data were test and non-test. The results of this research showed that the application of scientific learning using visual media can improve the percentege of learning mastery with minimum completeness criteria of more than 70 in the first cycle 74.33%, in the second cycle 82.60%, and in the third cycle 88.60%. Keywords: scientific approach, visual media, social science Abstrak: Penerapan Pendekatan Saintifik dengan Media Visual dalam Peningkatan Hasil Belajar IPS Tentang Perjuangan Para Tokoh Mempersiapkan Kemerdekaan Pada Siswa Kelas V SDN Watuduwur Tahun Ajaran 2015/2016. Tujuan penelitian meningkatkan hasil belajar IPS. Penelitian ini merupakan Penelitian Tindakan Kelas kolaboratif dilaksanakan dalam tiga siklus.Subjek penelitian adalah siswa kelas V SDN Watuduwur tahun 2015/2016, berjumlah 35 siswa.Validitas data menggunakan teknik triangulasi yang berupa triangulasi sumber data dan teknik pengumpulan data.Sumber data dalam penelitian ini yaitu siswa kelas V, guru kelas V,  dan dokumen. Teknik pengumpulan data yang digunakan yaitu tes dan nontes. Hasil penelitian menunjukkan bahwa penerapan pendekatan saintifik dengan media visual dapat meningkatkan persentase ketuntasan hasil belajar dengan KKM ? 70 pada siklus I sebesar 74,33%, siklus II 82,60%, dan siklus III 88,60%. Kata kunci: pendekatan saintifik, media visual, IPS